2016
DOI: 10.1073/pnas.1610716113
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid fibrils from the N-terminal prion protein fragment are infectious

Abstract: Recombinant C-terminally truncated prion protein PrP23-144 (which corresponds to the Y145Stop PrP variant associated with a GerstmannSträussler-Scheinker-like prion disease) spontaneously forms amyloid fibrils with a parallel in-register β-sheet architecture and β-sheet core mapping to residues ∼112-139. Here we report that mice (both tga20 and wild type) inoculated with a murine (moPrP23-144) version of these fibrils develop clinical prion disease with a 100% attack rate. Remarkably, even though fibrils in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 48 publications
1
70
0
Order By: Relevance
“…Moreover, structures of amyloid cores of Y145Stop-mutant PrP investigated with ssNMR was available although not in atomic resolution [16][37]. As amyloids of the Y145Stop-mutant induced infectious PrP Sc and caused bona fide prion disease when inoculated in mice [38], the amyloid could share the similar local structures with full-length PrP Sc . We therefore tentatively modeled local structures of PrP Sc in a region 107-143, PrP(107-143), utilizing the structural model of the Y145Stop mutant propounded by Theint et al [37] and the knowledge from the αSyn amyloid for stable β-arches, i.e., hydrophobic contact networks and the absence of Cβ-branched residues in a U-shaped loop ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, structures of amyloid cores of Y145Stop-mutant PrP investigated with ssNMR was available although not in atomic resolution [16][37]. As amyloids of the Y145Stop-mutant induced infectious PrP Sc and caused bona fide prion disease when inoculated in mice [38], the amyloid could share the similar local structures with full-length PrP Sc . We therefore tentatively modeled local structures of PrP Sc in a region 107-143, PrP(107-143), utilizing the structural model of the Y145Stop mutant propounded by Theint et al [37] and the knowledge from the αSyn amyloid for stable β-arches, i.e., hydrophobic contact networks and the absence of Cβ-branched residues in a U-shaped loop ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we also demonstrated that amyloid fibrils generated from mouse PrP23-144 are bona fide prions, causing transmissible prion diseases in mice (Choi et al, 2016). The key insight furnished by initial studies which relied on low-resolution biochemical and biophysical approaches (Kundu et al, 2003; Vanik et al, 2004; Jones and Surewicz, 2005) was that the cross-seeding specificities of human, mouse and Syrian hamster PrP23-144 amyloids (also referred to as [hu], [mo] and [Sha], respectively, for brevity) were encoded in their molecular conformations, with the latter notably found to be distinct in spite of high levels of sequence identity between the different PrP23-144 variants.…”
Section: Biological Contextmentioning
confidence: 93%
“…Other important properties of amyloid fibrils, such as the polymorphism (4,5,17) and the cross-seeding ability (6)(7)(8), also have been studied to elucidate the molecular basis underlying the pathogenic conversion. Although there are significant differences between amyloid fibrils and PrP Sc , including the degree of infectivity and the folding of N-terminal residues (18)(19)(20)(21)(22), the ability of amyloid fibrils to induce the onset of prion diseases in transgenic mice engineered to overexpress PrP suggests that these b-rich aggregates share a major characteristic (23,24).…”
mentioning
confidence: 99%